Building Tourism and Sociopetal Cultural Understanding Through Proxemics Sharing of Authentic Artefacts from the Tongkonan of North Toraja, Indonesia - Mediana Tobing, Melati; Sumilat Paembonan, Linda (International Journal of Engineering and Technology, 2018)
Existing theories of intercultural communication recognize each communication act as an authentic space that is filled with symbols that have cultural context. In the sense, that a group of signs will have different meanings for people of different cultures. In proxemics theory, sociofugal and sociopetal axis explain nonverbal factors of a place, which can attract or restrain the engagement of people in communications. Tongkonan, the dominant culture in the Indonesian region of North Toraja, has frightening death symbols, which have become a major attraction and talking point for visitors. Travellers observe and learn about these symbols and are also encouraged to share this learning with friends and relatives. The North Toraja tourism industry has come to recognize that this word of mouth promotion is more effective than media coverage in promoting both tourism and cultural awareness among outsider communities. This research involved observation study plus interviews with tourists in Kete Kesu Village in North Toraja in order to found interest both local Indonesian and international tourists in interacting with fixed-feature space, semi fixed-feature space, and person-to-person space in Tongkonan. A number of typical Tongkonan symbols such as buffalo horns, human skulls and jaws of animal victims, that normally restrain the desire of people to communicate, in this case, become an attraction in intercultural communication.Â